2016
DOI: 10.1039/c6nj02069k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of novel imidazo[4,5-c]pyridine derivatives as antimycobacterial agents against Mycobacterium tuberculosis

Abstract: Novel imidazo[4,5-c]pyridine derivatives showed cytotoxicity and decreased the bacterial load in lung and spleen tissues in the in vivo animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The in vitro activity of imidazole derivatives along with the references against Mycobacterium tuberculosis (ATCC 35801) were performed as previously described . Briefly, MIC for the compounds was determined by an agar dilution method.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro activity of imidazole derivatives along with the references against Mycobacterium tuberculosis (ATCC 35801) were performed as previously described . Briefly, MIC for the compounds was determined by an agar dilution method.…”
Section: Methodsmentioning
confidence: 99%
“…After primary screening of the toxicity studies, compounds 83a and 93b appeared to be the best potent molecule with minimum cytotoxicity. Prashanth et al synthesized imidazo[4,5-c]pyridine derivatives and evaluated their antimicrobial activity (Madaiah et al, 2016). The synthesis of the desired compound involved a series of reactions initiating from the chlorination of 2,6dichloropyridine 94 in the presence of trifluoroacetic acid, H 2 O 2 and POCl 3.…”
Section: Scheme 28mentioning
confidence: 99%
“…[4,5] Furthermore, several thiazolidine derivatives have been reported for a variety of biological activities apart from synthetic interests, [6][7][8][9] antibacterial, [10] anti-inflammatory, cardiovascular, hypoglycemic, lipid lowering, [11,12] and anti-oxidant activity. [13] In addition, a series of heterocyclic compounds bearing a pyridine moiety observed that the pyridine ring plays a vital role in many biological activities such as antimicrobial, [14][15][16] antiviral, [17,18] anti-convulsant, [19] and anti-mycobacterial. [20] Polysubstituted pyridine containing cyano group exhibited antitumor activity in numerous publications.…”
Section: Introductionmentioning
confidence: 99%